Use of kisspeptin to trigger oocyte maturation during in vitro fertilisation (IVF) treatment - Sharma, Bhavna; Koysombat, Kanyada; Comninos, Alexander N.; Dhillo, Waljit S.; Abbara, Ali (Frontiers in Endocrinology, 2022)
Infertility is a major global health issue and is associated with significant psychological distress for afflicted couples. In vitro fertilisation (IVF) utilises supra-physiological doses of stimulatory hormones to induce the growth of multiple ovarian follicles to enable surgical retrieval of several oocytes for subsequent fertilisation and implantation into the maternal endometrium. The supra-physiological degree of ovarian stimulation can lead to potential risks during IVF treatment, including ovarian hyperstimulation syndrome (OHSS) and multiple pregnancy. The choice of oocyte maturation trigger, such as human chorionic gonadotrophin (hCG) or gonadotrophin releasing hormone agonist (GnRHa), can impact both the efficacy of IVF treatment with a bearing on luteal phase hormonal dynamics and thus the degree of luteal phase support required to maintain optimal pregnancy rates, as well as on safety of treatment with particular respect to the risk of OHSS. Kisspeptin regulates gonadotrophin releasing hormone (GnRH) release and is therefore a key regulator of the hypothalamo-pituitary-gonadal (HPG) axis. Kisspeptin has been shown to be requisite for the occurrence of the physiological ovulatory luteinising hormone (LH) surge. In this review, we discuss the potential use of kisspeptin as a novel trigger of oocyte maturation.